Impact of high-protein, low-calorie diet on anthropometric indices, glycation, and inflammation associated with the fat mass and obesity (FTO) gene among individuals with overweight/obesity - Hajira, Bibi; Sehar, Bismillah; Fakhrunisa,; Siraj, Sami; Malik, Muhammad Omar; Naqeeb, Huma; Almajwal, Ali Madi; AlBlooshi, Sharifa; Hasan, Hayder; Alam, Iftikhar; Zeb, Falak; Lodhi, Fahad (Frontiers in Nutrition, 2025)
BackgroundThe common polymorphism rs9939609 of the fat mass and obesity gene (FTO) has been associated with increased susceptibility to obesity, but this association appears to be modified by diet. High protein diets have been shown to reduce weight and may increase the formation of circulating advanced glycation end products (AGEs). Obesity, on the other hand, is also associated with increased formation of AGEs, leading to oxidative stress and inflammation.ObjectivesThis study was designed to investigate the impact of a high-protein and low-calorie (HPLC) diet on anthropometric indices and circulating AGEs levels associated with the FTO variant rs9939609 among overweight/obese individuals.MethodsIn this interventional study, 60 overweight and obese individuals (aged 18–50 years) with no comorbidity were assigned to an HPLC diet of 800 kcal and ~100 g protein/day for 4 weeks. The enrolled participants were divided into three groups (each group, n = 20) based on FTO genotyping, i.e., AA, TT, and AT, using whole blood samples. Body mass index (BMI), waist circumference (WC), hip circumference (HC), and waist-to-hip ratio (WHR) were measured before and after intervention. Serum analysis of carboxymethyl lysine (CML) and interleukin-6 (IL-6) was performed at baseline (day 0) and at the endline (day 28).ResultsThe weight (p = 0.01), WC (p = 0.002), and WHR (p = 0.04) were significantly different among the three genotypes. The risk allele group (AA) had a higher mean weight (95.74 ± 19.13 kg), WC (105.85 ± 14.55 cm), and WHR (0.93 ± 0.08) compared with the wild-type TT. HPLC diet significantly decreased weight (p = 0.02), BMI (p = 0.03), WC (p < 0.001), and WHR (p = 0.02), while no significant effect was found on CML and IL-6 in all three genotypes at the end of intervention. The effect size estimates indicated significant variation explained by the FTO gene in weight (η2 = 0.158), BMI (η2 = 0.114), WC (η2 = 0.235), and WHR (η2 = 0.138).ConclusionThis study concludes that an HPLC diet modifies the variation of the FTO rs9939609 genotype and anthropometric measurements. These findings also suggest that high dietary protein intakes may protect against the obesogenic effects of FTO risk genotypes, leading to weight loss and improved metabolic parameters.